Osteopathology in the Equine Distal Phalanx Associated With the Development and Progression of Laminitis. (September 2015) - Engiles, J. B.; Galantino-Homer, H. L.; Boston, R.; McDonald, D.; Dishowitz, M.; Hankenson, K. D.
Although the equine distal phalanx and hoof lamellae are biomechanically and physiologically integrated, bony changes in the distal phalanx are poorly described in laminitis. The aims of this study were (1) to establish a laminitis grading scheme that can be applied to the wide spectrum of lesions seen in naturally occurring cases and (2) to measure and describe changes in the distal phalanx associated with laminitis using micro–computed tomography (micro-CT) and histology. Thirty-six laminitic and normal feet from 15 performance and nonperformance horses were evaluated. A laminitis grading scheme based on radiographic, gross, histopathologic, and temporal parameters was developed. Laminitis severity grades generated by this scheme correlated well with clinical severity and coincided with decreased distal phalanx bone volume and density as measured by micro-CT. Laminitic hoof wall changes included progressive ventral rotation and distal displacement of the distal phalanx with increased thickness of the stratum internum–corium tissues with lamellar wedge formation. Histologically, there was epidermal lamellar necrosis with basement membrane separation and dysplastic regeneration, including acanthosis and hyperkeratosis, corresponding to the lamellar wedge. The changes detected by micro-CT corresponded to microscopic findings in the bone, including osteoclastic osteolysis of trabecular and osteonal bone with medullary inflammation and fibrosis. Bone changes were identified in horses with mild/early stages of laminitis as well as severe/chronic stages. The authors conclude that distal phalangeal pathology is a quantifiable and significant component of laminitis pathology and may have important implications for early detection or therapeutic intervention of equine laminitis.